WWLLN Hot and Cold-Spots of Lightning Activity and Their Relation to Climate in an Extended Central America Region 2012–2020 - Amador Astúa, Jorge Alberto (2022)
Lightning activity has been recognized to have, historically, social and environmental consequences around the globe. This work analyzes the space-time distribution of lightning-densities (D) in an extended Central America region (ECA). World Wide Lightning Location Network data was analyzed to link D with dominant climate patterns over the ECA for 2012–2020. D associated with cold surges entering the tropics dominate during boreal winter. The highest D (hot-spots) was found to agree well with previously known sites, such as the “Catatumbo” in Venezuela; however, D was lower here due to different detection efficiencies. Previously reported hot-spots showed strong continental signals in CA; however, in this work, they were over the oceans near to coastlines, especially in the eastern tropical Pacific (ETP). Most cold-spots, implying a minimum of vulnerability to human impacts and to some industries, were situated in the Caribbean Sea side of Central America. The Mid-Summer-Drought and the Caribbean-Low-Level-Jet (CLLJ) markedly reduced the D during July-August. The CLLJ in the central CS and across the Yucatan and the southern Gulf of Mexico acts as a lid inhibiting convection due to its strong vertical shear during the boreal summer. The CLLJ vertical wind-shear and its extension to the Gulf of Papagayo also diminished convection and considerably decreased the D over a region extending westward into the ETP for at least 400–450 km. A simple physical mechanism to account for the coupling between the CLLJ, the MSD, and lightning activity is proposed for the latter region.